First Descriptions of the ocean-collected first Crabs of Etisus sp. (Crustacea: Brachyura: Portunidae) from the Saudi Arabian Red Sea - Naqoor, Nada; Austin, Anand (Journal of King Abdulaziz University: Marine Sciences, 2025)
No first crab of the genus Etisus has been described yet. Thirty five megalops of an Etisus sp. were collected from Obhur Creek, Jeddah, Saudi Arabia and reared in the laboratory upto first crab stage. These first crabs were identified using molecular barcode methods and morphologically described herein and compared with those of the two species of Xanthoidean crabs, Eurytium limnosum and Leptodius exaratus. Apart fromsome minor variations, three characters differentiate the first crabs of the present study with those of the other two species: presence of several minute spines on the basal segment of the peduncle of antennule, presence of crista dentate in the endopod of third maxilliped and serrated lateral margins of third abdominal segment.